Quantitative CNV testing in molecular diagnostics - Stavropoulos, Dimitri J. (Henry Stewart Talks, 2021)
Copy number variants (CNV), Brief history of hereditary genomic rearrangements and disease, Methods of CNV detection, Exon targeted dosage analysis, Multiplex ligation probe amplification (MLPA), Microarray, Criteria for the determination of CNV detection, Clinical interpretation and reporting of CNVs